Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Guru SMPN 2 Puspahiang - Cucu Cahyati; Barin Barlian; Titin Patimah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the effect of leadership style and work motivation on teacher performance at SMPN 2 Puspahiang. The method used in this research is cuntitative through a survey approach. In this study, the sample taken was the entire population of teachers at SMPN 2 PUSPAHIANG, the population of which was 42 teachers. The data used is primary data. The analytical tool used in this research is multiple regression using SPSS 26.0. The results of the research show that the Leadership Style obtained from the Teachers of SMPN 2 Puspahiang has good criteria. Work Motivation for SMPN 2 Puspahiang Teacher products has good assessment criteria, Teacher Performance for SMPN 2 Puspahiang Teachers has good assessment criteria. Together Leadership Style and work motivation have a significant influence on Teacher Performance. Partially Leadership Style has a significant influence on Teacher Performance. Partially, work motivation has a positive and significant effect on teacher performance.